2018
DOI: 10.1016/j.jcf.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple prevalent fractures in relation to macroscopic bone architecture in patients with cystic fibrosis

Abstract: Bone densitometry is a useful tool for noninvasive assessment of fracture risk in CF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 26 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…[ 3 ] A more recent study by Stahl et al demonstrated that several pQCT parameters, including SSI and trabecular BMD at the distal radius, are able to differentiate between CF patients with 1 fracture or less and those with more than one fracture. [ 24 ] Finally, a study by Bai et al compared pQCT results at the radius in children ages 7–18 years with CF with healthy controls. [ 25 ] They found that although the children with CF had thicker cortical bone, they still had reduced bone strength compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] A more recent study by Stahl et al demonstrated that several pQCT parameters, including SSI and trabecular BMD at the distal radius, are able to differentiate between CF patients with 1 fracture or less and those with more than one fracture. [ 24 ] Finally, a study by Bai et al compared pQCT results at the radius in children ages 7–18 years with CF with healthy controls. [ 25 ] They found that although the children with CF had thicker cortical bone, they still had reduced bone strength compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical bone composition and density are key determinants of bone strength and fracture risk in humans [18] . Recent studies reported an elevated fracture rate in CF patients [ 5 , 12 , 31 ] in relation with macroscopic bone architecture [32] , and others described deficits in trabecular and cortical bone as well as strength in prepubertal children, adolescents and adults with CF [ 8 , 33-35 ]. People with CF have several risk factors to develop low bone mass and density including chronic lung inflammation, pancreatic insufficiency, malnutrition, delayed puberty, glucocorticoid use, and possibly CFTR dysfunction itself [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Well done cross-sectional and longitudinal studies have indicated diminished bone accrual during the skeletal formative period of late childhood and adolescence [11,13,14] . A recent report showed a 9-fold higher fracture rate in young German CF adults compared to the age-matched reference population [15] . It is still unknown if the smaller stature in CF patients is a direct cause of loss of CFTR or a manifestation of nutritional deficiencies and inflammation [16] .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Low bone mineral density (BMD) is a common complication of CF, and microarchitecture assessment by high‐resolution peripheral scanner showed impaired volumetric density . The severity of the lung disease is the main determinant of bone loss, leading to increased fracture risk, selectively in the spine and ribs . Nevertheless, despite the improvement of care over recent years, a significant number of patients with CF had low BMD Z scores and reported fractures .…”
Section: Metabolic Bone Diseasementioning
confidence: 99%